Genetic and biophysical modelling evidence of generational connectivity in the intensively exploited, Western North Atlantic red grouper (Epinephelus morio) - Bernard, Andrea M; Johnston, Matthew W; Pérez-Portela, Rocío; Oleksiak, Marjorie F; Coleman, Felicia C; Shivji, Mahmood S (ICES journal of marine science, 2020)
Abstract Understanding the connectivity of reef organisms is important to assist in the conservation of biological diversity and to facilitate sustainable fisheries in these ecosystems. Common methods to assess reef connectivity include both population genetics and biophysical modelling. Individually, these techniques can offer insight into population structure; however, the information acquired by any singular analysis is often subject to limitations, underscoring the need for a multi-faceted approach. To assess the connectivity dynamics of the red grouper (Epinephelus morio), an economically important reef fish species found throughout the Gulf of Mexico and USA western Atlantic, we utilized two sets of genetic markers (12 microsatellite loci and 632 single nucleotide polymorphisms) to resolve this species’ population genetic structure, along with biophysical modelling to deliver a spatial forecast of potential larval “sources” and “sinks” across these same regions and spatial scale. Our genetic survey indicates little, if any, evidence of population genetic structure and modelling efforts indicate the potential for ecological connectivity between sampled regions over multiple generations. We offer that using a dual empirical and theoretical approach lessens the error associated with the use of any single method and provides an important step towards the validation of either of these methodologies.